Good neighbors - Tedrow, Thomas L. (Nashville : T. Nelson Publishers, 1992)
In Mansfield, Missouri, during the harsh winter of 1905, Laura, her family, and her neighbors help each other survive and discover the true meaning of Christmas.
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Frontier and pioneer life -- Missouri -- Fiction; Farm life -- Missouri -- Fiction; Christmas stories; Missouri -- Fiction